2016
DOI: 10.1093/pm/pnw152
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Provides Pain Relief with Improved Psychosocial Function: Results from EMP3OWER

Abstract: Spinal cord stimulation provided pain relief and significant improvement of patient psychological and functional outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
7
19
1
Order By: Relevance
“…Besides these significant results, our results show an increase of values for positive mood, and a reduction in values for desperation, sorrow, fatigue, and anger in the whole follow-up period after PNFS implantation on ASTS, a German modified version of the POMS. Our findings suggest, like Rosenberg et al for SCS treatment reported, that PNFS in patients with chronic low back pain reduces the level of mental disturbance, anxiety, anger, and fatigue and thus stabilizes patients' psychological state through pain reduction (47). Kloimstein et al showed a reduction, even not significant, of the degree of depression measured on Beck Depression Inventory (21).…”
Section: Discussionsupporting
confidence: 79%
“…Besides these significant results, our results show an increase of values for positive mood, and a reduction in values for desperation, sorrow, fatigue, and anger in the whole follow-up period after PNFS implantation on ASTS, a German modified version of the POMS. Our findings suggest, like Rosenberg et al for SCS treatment reported, that PNFS in patients with chronic low back pain reduces the level of mental disturbance, anxiety, anger, and fatigue and thus stabilizes patients' psychological state through pain reduction (47). Kloimstein et al showed a reduction, even not significant, of the degree of depression measured on Beck Depression Inventory (21).…”
Section: Discussionsupporting
confidence: 79%
“…SCS is considered an appropriate and efficacious treatment option for a number of overlapping diagnoses between the cervical and lumbar spine: radiculopathy , CRPS , neuropathic pain . It is this overlap that gives neuromodulators the confidence to use SCS on other less established indications where there may be little evidence to support such use.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected and combined from two previously published institutional review board‐approved, prospective, multicenter registries—the EMPOWER and PAIN registry studies (Abbott, formerly St. Jude Medical). All patients treated with SCS in this study were done so utilizing standard tonic programming algorithms, at or under 1500 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of cervical SCS for treating cervical radiculopathy and complex regional pain syndrome has been established . Nevertheless, there is a lack of published evidence to support the claim that SCS is effective for postsurgical pain in the cervical region.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of cervical SCS for treating cervical radiculopathy and complex regional pain syndrome has been established. [46][47][48] Nevertheless, there is a lack of published evidence to support the claim that SCS is effective for postsurgical pain in the cervical region. A retrospective analysis of a prospectively maintained multicenter registry by Deer and colleagues, with a mean follow-up of 88 months, found that cervical SCS was associated with enhanced pain relief, quality of life, and patient satisfaction, as well as a statistically significant improvement in pain disability index (PDI) in a group of 38 patients.…”
Section: Discussionmentioning
confidence: 99%